Proof-of-concept: 3D bioprinting of pigmented human skin constructs - Ng, Wei Long (2018)
Three-dimensional (3D) pigmented human skin constructs have been fabricated using a 3D bioprinting approach. The 3D pigmented human skin constructs are obtained from using three different types of skin cells (keratinocytes, melanocytes and fibroblasts from three different skin donors) and they exhibit similar constitutive pigmentation (pale pigmentation) as the skin donors. A two-step drop-on-demand bioprinting strategy facilitates the deposition of cell droplets to emulate the epidermal melanin units (pre-defined patterning of keratinocytes and melanocytes at the desired positions) and manipulation of the microenvironment to fabricate 3D biomimetic hierarchical porous structures found in native skin tissue. The 3D bioprinted pigmented skin constructs are compared to the pigmented skin constructs fabricated by conventional a manual-casting approach; in-depth characterization of both the 3D pigmented skin constructs has indicated that the 3D bioprinted skin constructs have a higher degree of resemblance to native skin tissue in term of the presence of well-developed stratified epidermal layers and the presence of a continuous layer of basement membrane proteins as compared to the manually-cast samples. The 3D bioprinting approach facilitates the development of 3D in vitro pigmented human skin constructs for potential toxicology testing and fundamental cell biology research.